A CT-Based Simulation Study to Compare the Risk of Facet Joint Violation by the Cervical Pedicle Screw Between Degenerative and Nondegenerative Cervical Spines. Issue 3 (February 2017) - Lee, Dong-Ho; Noh, Hyounmin; Hwang, Chang Ju; Lee, Choon Sung; Abumi, Kuniyoshi; Cho, Jae Hwan
Abstract : Study Design: A retrospective case-control study. Objective: This study aimed (A) to compare entry points and trajectories of the cervical pedicle screw (CPS) between degenerative and nondegenerative spines, and (B) to evaluate the risk of facet joint violation by the CPS according to the degree of facet degeneration. Summary of Background Data: Entry point, trajectories, and risk of misplacement of the CPS have been widely researched; however, its application to degenerative cervical spine has to be elucidated. Methods: Sixty patients who underwent cervical surgeries at our institution were classified into two groups according to cervical facet joint degeneration. A simulation program with 0.7-mm thickness axial computed tomographic images was used to evaluate facet joint violation by the CPS from C3 to C6. Horizontal and vertical offsets of entry points were measured from two different anatomical landmarks on lateral mass, namely the lateral notch and the center of the superior ridge. The transverse and sagittal angles of the screws were also measured. Facet joint violation was evaluated and classified into either "minor" (<50% of screw diameter) or "major" (≥50% of screw diameter). Results: The mean transverse and sagittal angles showed no difference between the two groups. However, a more superior vertical offset from the superior ridge in terms of entry point was observed in the degenerative cervical spine group at all levels ( P  = 0.001–0.026). In addition, facet joint violation was more frequently found in severely degenerated facet joints than in mild to moderately degenerated facet joints ( P  = 0.011). Conclusion: The entry point of CPS was moved more superiorly in the degenerative cervical spine in this study, which increased the risk of facet joint violation in our patients. Thus, surgeons need to modify the insertion technique of the CPS or to insert lateral mass screw instead of the CPS when it is considered to insert screws at the uppermost vertebra in the degenerative cervical spine. Level of Evidence: 4